Labour Market Policy under Conditions of Permanent Austerity: Any Sign of Social Investment?. (3rd February 2017) - Bengtsson, Mattias; de la Porte, Caroline; Jacobsson, Kerstin
Abstract: Social investment (SI) is part of a strategy to modernize the European welfare states by focusing on human resource development throughout the life‐course, while ensuring financial sustainability. Recognizing that this strategy was only partially implemented by the EU member states prior to the financial and Eurozone crises, this article investigates whether reforms and expenditure patterns in labour market policy (LMP) have moved more towards or away from SI following the 2008 financial crisis. We use quantitative and qualitative data to investigate the degree to which there have been shifts in the SI aspects of LMPs in eight countries across four welfare state regimes. We also investigate which aspects of LMPs have been strengthened and which have been weakened, enabling us to make a nuanced assessment of labour market SIs across the EU in a period of permanent austerity. We find that although the eight countries under examination have different starting points, there is little evidence of increased SI‐orientation of LMPs. Upskilling, which is at the heart of SI, did not increase from 2004–08 to 2009–13, while incentive reinforcement and employment assistance – more about labour market entry and marketing of skills – grew in importance. If this trend continues across Europe, there is a risk that SI will become lost in translation and end up as a clearer neo‐liberal version of workfarism.